Green transition for whom? Exploring local narratives of green transition and sacrifice in Gällivare municipality - Mårtensson,Alva (2025)
How can we understand Gällivare municipality as a sacrifice zone through local narratives of green transition? The transition to low-carbon economies in the wake of the European Green Deal drives increased demands for metals and minerals, renewable energy, biomass from forests – intensifying green extractivism. In Gällivare municipality, located in the rural north of Sweden and within the borders of the Indigenous Sápmi, such extractive pressures raise questions of social and environmental sustainability and justice. This thesis takes a holistic, interpretive approach to explore the experience of living in the municipality during this time by studying local narratives of green transition as a whole. The contributors consist of two local politicians, a representative from a Sámi village, and two persons engaged in a local branch of an environmental organization. The narratives are analysed using a conceptual framework structured around the concept of green sacrifice zones, referring to areas bearing a disproportionate burden of the extractivism of natural resources. While the approach provided rich insights into the studied experiences, a conclusion of this thesis is that the broad scope also put limits to the analysis.
Keywords: Green transition; green extractivism; green sacrifice zones; narratives